Ion Beams: In Situ Mitigation of Subsurface and Peripheral Focused Ion Beam Damage via Simultaneous Pulsed Laser Heating (Small 13/2016). Issue 13 (April 2016) - Stanford, Michael G.; Lewis, Brett B.; Iberi, Vighter; Fowlkes, Jason D.; Tan, Shida; Livengood, Rick; Rack, Philip D.
Abstract : Focused ion beam (FIB) processing is an important direct‐write nanoscale synthesis technique; however it generates subsurface defects that can preclude its use for many applications. On page 1779 P.D. Rack and co‐workers demonstrate an in situ laser assisted focused ion beam synthesis approach, which photothermally mitigates the defects generated in silicon during focused He + and Ne + exposures. Finally, the group shows that laser assisted FIB reduces the damage generated in graphene nanochannels fabricated via the He + FIB.